Neurolinguistic programming and sectarian groupings (Rivista di Psicopatologia Forense, Medicina Legale, Criminologia, 2021)
In the paper there are descriptions of the different types of sects to fully understand how they differ and which is the focal center of the movements. Subsequently, we will analyze the techniques of mental control and manipulation that take place in the different sectarian groupings and how it works and what is NLP (neurolinguistic programming) used very frequently by leaders to lure followers and consequently to keep them within the group. Finally, the problems of this phenomenon will be highlighted to sensitize the community to the issue under consideration.